Unbreakable how to prepare yourself for a strong relationship - Aiman Azlan (Iman Publication Sdn Bhd, 2019)
For the singles who are searching of love, is there a to know if you are ready to commit yourself to a relationship? For the couples, is there a method to making the relationship last? Is love a matter of the heart and emotions, or can love be managed in a logical and practical manner? In Unbreakable, author and Youth Mentor Aiman Azlan encourages us to change our perspective when it comes to love and relationship that it is not something you fall into but something that you need to prepare and work for. For there is a difference between falling in love and staying in love. Not only does this book provides practical steps towards managing love, but it also guides readers on how to embrace and navigate the emotional aspect of interhuman relationship so that love can withstand the tests and challenges of life.